إشكالية تأسيس الجمعيات بالمغرب "بين التصريح والترخيص" - عيدون، عادل (رضوان العنبي, 2022)
إن حرية تأسيس الجمعيات بالمغرب تتمظهر من خلال الميكانيزمات القانونية، بين تحقيق المكتسبات وبين انتكاساتها أو تراجعها، وهو ما تأكد من خلال الممارسة، فرغم توفر المغرب على إطار قانوني وتنظيمي متقدم في هذا المجال، يسجل على مستوى الممارسة عدم تفعيل هاته النصوص التنظيمية وإصرار السلطات المعنية على تجاوز الاختصاصات الموكولة لها في هذا المجال. وهذا ما تم تسجيله من طرف العديد من المنظمات الدولية والوطنية، التي ما فتئت تسجل في تقاريرها تطاول الإدارة على اختصاص السلطة القضائية المتمثلة في تقدير أحقية الجمعيات في التأسيس من دونه، وهو ما تتصدى له المحاكم المختص بمختلف مستوياتها بشكل مستمر، إذ تواترت الأحكام المتعلقة بإلغاء قرارات السلطة الإدارية الرامية إلى الحد من حرية تأسيس الجمعيات.
The freedom of establishing associations in Morocco is manifested through a set of statutory mechanisms and through accomplishments achieved and setbacks suffered in practice. Although the Moroccan authorities are offering a progressive legal and Regulatory framework for the establishment of associations, its application has not come into effect as authorities insist on misusing and exceeding their functions as prescribed by law. These violations of the right to establish associations have been reported by several national and international organizations which constantly publish, in their reports, the encroachments of the administrative authorities upon the role of the judicial authorities when deciding on the eligibility of establishing associations, which is an exclusive judicial function. The Moroccan courts responded to such administrative maneuvers by recurrent revocation of the arbitrary rulings, issued by administrative authorities, meant to restrict the freedom of establishing associations.
Keywords: الجمعيات الأهلية -- حقوق الإنسان -- السلطات الإدارية -- التنظيم القانوني -- المغرب